2018
DOI: 10.21873/anticanres.13056
|View full text |Cite
|
Sign up to set email alerts
|

LC3A, LC3B and Beclin-1 Expression in Gastric Cancer

Abstract: Background: The current study examined the key proteins involved in autophagosome formation and their prognostic role in gastric cancer. Materials and Methods: Paraffin-embedded tissues from 121 consecutive patients treated with surgery for gastric cancer were analyzed immunohistochemically for the expression of autophagic proteins microtubule-associated proteins 1A/1B light chain 3A and 3B (LC3A, LC3B) and beclin-1 (encoded by BECN1 gene). Assessment of proliferative index using E3 ubiquitin-protein ligase (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…Dysfunction of autophagy is involved in multiple human diseases (Levine and Kroemer, 2008;Liang, 2010), including cancer where autophagy plays a double role: in oncogenically challenged cells autophagy may prevent tumor progression by removing ROS and damaged mitochondria (White, 2012;Amaravadi and Debnath, 2014); on the other hand, in overt tumors, autophagy seems to contribute to tumor cell survival by promoting nutrient recycling and sustaining anti-apoptotic pathways (Levy et al, 2017;Mowers et al, 2017). Along with this line, increased autophagic flux has been reported for various types of tumors, including breast cancer (BC) (Lazova et al, 2012;Mikhaylova et al, 2012;Giatromanolaki et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Dysfunction of autophagy is involved in multiple human diseases (Levine and Kroemer, 2008;Liang, 2010), including cancer where autophagy plays a double role: in oncogenically challenged cells autophagy may prevent tumor progression by removing ROS and damaged mitochondria (White, 2012;Amaravadi and Debnath, 2014); on the other hand, in overt tumors, autophagy seems to contribute to tumor cell survival by promoting nutrient recycling and sustaining anti-apoptotic pathways (Levy et al, 2017;Mowers et al, 2017). Along with this line, increased autophagic flux has been reported for various types of tumors, including breast cancer (BC) (Lazova et al, 2012;Mikhaylova et al, 2012;Giatromanolaki et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Discussion. It is known that a high content of the LC3B protein of gastric tumors is one of the markers of the disease [Giatromanolaki A, 2019] and can predict the outcome of the disease . This study showed that LC3B expression is associated with tumor size and disease prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…The latter is a structural protein of autophagosome membranes and is widely used as a marker of this process. High levels of LC3B are found in gastric cancer cells [Giatromanolaki A, 2019] and can predict the disease's outcome .…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting Beclin-1 has been shown with compounds such as Spautin-1, a PI3KCIII/VSP34 complex inhibitor, which targets Beclin-1-induced autophagy (Table 2) [175]. Xestosponging B can also disrupt interactions between INS Fig.…”
Section: Beclinmentioning
confidence: 99%
“…Gastric cancer has been found to have autophagy activation in all of these manners. Targeting autophagy is being investigated with both mTOR inhibition, hypoxic gene inhibition, or deacetylation inducing compounds (see Table 2) [1,4,5] P3 membrane cargo loading and Beclin-1 [175]. These compounds have been tested preclinically in gastric cancer and have shown some therapeutic benefit in gastric cancer cell lines.…”
Section: Beclinmentioning
confidence: 99%